Hydrochloric acid removal from the thermogravimetric pyrolysis of PVC - Torres, Daniel; Jiang, Ying; Sanchez-Monsalve, D. A.; Leeke, Gary A. (Elsevier, 2020)
A powder characterization method was developed to screen the ability of a range of chemicals and absorbents to retain chlorine from chlorinated plastic pyrolysis. The behaviour of adsorbents such as Al2O3 and zeolites, and chemical removers based on NaHCO3, CaO and Na2CO3-ZnO were studied for the removal of HCl released during PVC pyrolysis. First, chlorine removers are mixed with PVC and tested in a thermobalance under pyrolysis conditions for the complete PVC dehydrochlorination (550 °C). Subsequently, after the release of HCl, CO2 and H2O, the chars are analysed by FTIR, CHN elemental analysis and ESEM-EDS to determine the retention of chlorine on the chlorine removers. According to FTIR and CHN, PVC pyrolysis occurs through dehydrochlorination and the formation of aromatics. FTIR and EDS were used to follow the consumption of the bases present in the chemical removers and the suppression of the CCl absorption bands of the PVC CHCl groups during pyrolysis, as well as the formation of the resulting salts (NaCl, CaCl2 and ZnCl2). The chemical removers exhibited chlorine retentions of up to 71 wt. % (using Na2CO3-ZnO), while the adsorbents presented a maximum of 19 % of retention at 550 °C and heating rate of 200 °C/min.
Keywords: Chlorine removal; PVC dehydrochlorination; PVC pyrolysis; Hydrochloric acid removers; Thermogravimetric analysis; FTIR